The Effect of Adding Cellulose on the Mechanical and Chemical Properties of the Cement - A. Addullah, Nadhim; A. AL.ghanim, Hameed; k. Husain, Haleem; A. Abood, Mothana (University of Thi-Qar Journal of Science, 2019)
In this study we focused on adding cellulose found in the covers of sun flower and this adding was in form of different ratio and constant size of these additive to the matrix of Iraqi cement ( Om Qasar factory for cement ) .the prepared samples was in form of cubic and evaluated as they were treated different ( water treatment, moisture treatment dry treatment ). All the prepared samples had a proportion of (3 /1 ) cement to sand and in the form of cubes with aside ( 50 mm ) long .they also had the the weight –rate of the added cellulose to the cement which was ( 1%- 5%) . The obtained results showed that the cement mixture that had the weight rate of 5% is the best as it has good mechanical properties ( flexural strength , splitting tensile, compressive strength ) .These properties have been used to study the resistance of the modified cement to the chemical agents that attack cement and concrete.